Felsőoktatás Kínában 1. : irányváltások és reformok Konfuciusztól a tömegoktatásig - Keczer, Gabriella (Közép-Európai Közlemények, 2015)
In a series of studies I analyse the past and present of Chinese higher education. The topic may be justified by the fact that up to now no comprehensive study has been published in Hungary about the long way China went along from the darkest years of communism to nowaday’s marketized, privatized, internationalized education. In this initial paper I summarize the changes in the directions in higher education policy from the beginning to the mass education of the 21th century. After giving a snapshot of the ancient roots and the middle ages, I give a detailed picture of the Mao-era when higher education was almost demolished in the frame of the so called Cultural Revolution. Then I give na account of the different reforms aiming to restore Chinese higher education after Mao Ce-tung. Finally I present the enormous extension of the system that made Chinese higher education the largest in the world. I build my analysis on international literature and statistical data.